2010
DOI: 10.1002/jmri.22136
|View full text |Cite
|
Sign up to set email alerts
|

Perforator flap magnetic resonance angiography for reconstructive breast surgery: A review of 25 deep inferior epigastric and gluteal perforator artery flap patients

Abstract: Purpose: To evaluate the accuracy of magnetic resonance angiography (MRA) for preoperative mapping of rectus and gluteal muscle perforating arteries prior to autologous flap breast reconstruction. Materials and Methods:Preoperative MRA on 25 consecutive patients undergoing perforator artery-based autologous breast reconstruction was performed at 1.5 T using 3D liver accelerate volume acquisition (LAVA) of abdominal or gluteal regions acquired during injection of 20 mL of gadobenate dimeglumine with bolus timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…As demonstrated by Ahmadzadeh et al (26), the majority of perforators are along the superior two-thirds of a line from the posterior superior iliac spine to the greater trochanter (16,27,28). The superior gluteal artery perforator pedicle length is usu- ally 5-7 cm and is measured from the point between the gluteus medius and piriformis muscles (16,28). This pedicle may course through or in between the gluteus maximus and gluteus medius muscles in a variety of orientations (9,27,28) (Fig 5).…”
Section: Superior Gluteal Artery Perforator Flapmentioning
confidence: 92%
See 1 more Smart Citation
“…As demonstrated by Ahmadzadeh et al (26), the majority of perforators are along the superior two-thirds of a line from the posterior superior iliac spine to the greater trochanter (16,27,28). The superior gluteal artery perforator pedicle length is usu- ally 5-7 cm and is measured from the point between the gluteus medius and piriformis muscles (16,28). This pedicle may course through or in between the gluteus maximus and gluteus medius muscles in a variety of orientations (9,27,28) (Fig 5).…”
Section: Superior Gluteal Artery Perforator Flapmentioning
confidence: 92%
“…The superior gluteal artery perforator flap is oriented transversely across the upper portion of the buttock, with the superior gluteal vessels oriented at the medial portion of the flap (Fig 4) (16). As demonstrated by Ahmadzadeh et al (26), the majority of perforators are along the superior two-thirds of a line from the posterior superior iliac spine to the greater trochanter (16,27,28). The superior gluteal artery perforator pedicle length is usu- ally 5-7 cm and is measured from the point between the gluteus medius and piriformis muscles (16,28).…”
Section: Superior Gluteal Artery Perforator Flapmentioning
confidence: 93%
“…As with abdominal flaps, this is typically performed via CTA, although magnetic resonance angiography has also been advocated for this purpose (Fig 12). 109 …”
Section: Flap Selectionmentioning
confidence: 97%
“…[39][40][41][42] Contrast enhanced MRA delineates accurately the intramuscular trajectory of the perforators and can identify vessels >0.8mm in diameter. 11,[40][41][42] Rozen et al suggested that despite high sensitivity (100%) MRA was inferior to preoperative CTA due to low specificity (50%), 43 while Chernyak et al reported a 97% concordance of MRA imaging with intraoperative findings in DIEP flap breast reconstruction. 44 Despite its higher cost, MRA has certain advantages over CTA, namely elimination of exposure to ionizing radiation and safer required contrast medium.…”
Section: Perforator Artery or Perforator Complex?mentioning
confidence: 99%
“…Nevertheless, gadolinium may also be nephrotoxic for patients with renal insufficiency. 11,12,[40][41][42][43][44] Masia et al demonstrated that non-contrast magnetic resonance imaging was associated with high specificity and provided reliable information on the perforator branching within the subcutaneous abdominal tissue and the vascular connections between the superficial and the deep inferior epigastric vessels 45 Nevertheless, a serious limitation of MRA is possible patient discomfort, as it requires breath-hold for 10-20 seconds to avoid motion artifacts. Distress levels may increase in claustrophobic patients, while the technique is contraindicated in severely obese and patients with metallic implants.…”
Section: Perforator Artery or Perforator Complex?mentioning
confidence: 99%